Social perception through the gaze in Jeffrey Eugenides’s The Virgin Suicides - Cholifah Nindya Rahmawati; Ruly Indra Darmawan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study explores how Jeffrey Eugenides’s novel The Virgin Suicides constructs social perception through the Lacanian concept of the Gaze. The narrative centers on the Lisbon sisters as the main characters, who are constantly observed, interpreted, and narrated by a collective voice. This research aims to analyze how the collective gaze constructs social meaning and contributes to the objectification and social silencing of the girls. By employing Lacanian psychoanalysis, focusing on the gaze, this study conducts a qualitative textual analysis of selected quotations from the novel. The findings reveal that social perception begins with observation, positioning the Lisbon sisters as objects. Their identities are shaped by dominant discourses such as religion, social norms, and law, which translate their experiences into socially acceptable meanings. The study argues that the novel critiques the mechanism of social perception, emphasizing how visible observation and interpretation take precedence over genuine understanding. By demonstrating how the collective gaze functions as a form of social control in the Symbolic Order, this research contributes to Lacanian literary studies. It offers a new perspective on the relationship between social perceptions through the collective gaze narrative in Eugenides’s work.